Pertanggungjawaban Perdata Dokter Berdasarkan Profesinya Sebagai Beroep Dan Bedrijf - Muhammad Nur Alamsyah; Vazrie Avicenna; Gusti Yosi Andri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Doctors in carrying out their profession have medical risks that must be accounted for where sanctions can be civil, criminal or administrative. This research aims to determine the differences in civil responsibilities of a doctor in terms of his profession as a beroep (person who carries out work) and a bedrijf (person who runs a company). The method used is normative juridical by connecting civil liability with the profession of a doctor as a doctor and doctor. Research’s result shows that there is a difference in civil liability between doctors as beroep and doctors as bedrijf. As a beroep, the fulfillment of responsibilities to third parties (patients) is carried out by the employer at the place of work, whereas as a bedrijf, the fulfillment of responsibilities is first seen in the form of the business entity that is established. The maatschaf form of business entity used in a doctor's practice will give rise to personal responsibility, while the firm form of business entity used in a doctor's practice will give rise to joint or joint liability.